System of activities implementing participatory techniques to improve english pronunciation. - Espinoza Orellana, Kareliz Andrea; Ramírez Cruz, Yalile Yelena (Machala: Universidad Técnica de Machala, 2024)
The main objective of this research was to improve the pronunciation of the students of third year of “Colegio de Bachillerato Nueve de Octubre” through the implementation of a system of activities using role-play as a participatory technique. To achieve this purpose, the analytical-synthetic, systematic, hypothetical-deductive and historical-logical methods were used within a quantitative experimental approach, Initially, a diagnosis was made by means of a pre-test to evaluate the students’ initial level of pronunciation. Subsequently, a series of role-play-based activities were designed and applied, which were specifically designed to improve students’ clarity, fluency and intelligibility. These activities included simulated scenarios where students practiced real communicative situations. After the implementation of the intervention program, a post-test was administered to measure the results obtained. The data collected were analyzed statistically, using mean comparison test, which allowed us to confirm the hypothesis put forward and demonstrate that the implementation of the role-play contributed significantly to the improvement of students’ pronunciation. The results revealed a remarkable improvement in the participants’ accuracy and fluency, thus validating the effectiveness of the proposed approach. This study not only contributes to the field of English language teaching in educational contexts, but also provides theoretical and practical foundations for future research around participatory methodologies and their impact of the acquisition of language skills.
La presente investigación tuvo como objetivo principal mejorar la pronunciación de los estudiantes de tercero de bachillerato del Colegio Nueve de Octubre a través de la implementación de un sistema de actividades utilizando como técnica partitiva el role-play. Para lograr este propósito, se emplearon métodos analítico-sintético, sistemático, hipotético-deductivo e histórico-lógico, dentro de un enfoque cuantitativo experimental, Inicialmente, se realizó un diagnóstico mediante un pretest para evaluar el nivel inicial de pronunciación de los estudiantes. Posteriormente, se diseñaron y aplicaron una serie de actividades basadas en role-play, las cuales fueron diseñadas específicamente para mejorar la claridad, fluidez e inteligibilidad de los estudiantes. Estas actividades incluyeron escenarios simulados donde los estudiantes practicaron situaciones comunicativas reales. Tras la implementación del programa de intervención, se administró un post test para medir los resultados obtenidos. Los datos recopilados fueron analizados estadísticamente, utilizando pruebas de comparación de medias, lo cual permitió confirmar la hipótesis planteada y demostrar que la implementación del role-play contribuyó significativamente a la mejorar de la pronunciación de los estudiantes. Los resultados revelaron un avance notable en la claridad, fluidez e inteligibilidad en la pronunciación de los participantes, validando así la efectividad del enfoque propuesto. Este estudio no solo contribuye al campo de la enseñanza del idioma inglés en contextos educativo, sino que también proporciona fundamentos teóricos y prácticos para futuras investigaciones en el área de metodologías participativas y su impacto en la adquisición de las habilidades lingüísticas.
Keywords: PRONUNCIACION; ROLE-PLAY; SISTEMA DE ACTIVIDADES; TECNICAS PARTICIPATIVAS